Understanding school design processes. (1st December 2014) - Kowaltowski, Doris Catharine Cornelie Knatz; Deliberador, Marcella Savioli
This paper presents the results of an investigation of the design process of school buildings in the state of São Paulo in Brazil. The study was based on structured interviews with the architects who in the last decade designed schools for the local school building agency – Fundação para o Desenvolvimento da Educação (FDE). Guiding principles for the questionnaire were extracted from the literature on high-performance school design processes. The results show that the design process is primarily influenced by the agency FDE. This process was compared to recommendations found in the literature. Some opportunities for change could be identified and the characterisation indicates the need for better assessment tools and access to technical information directly applicable to design issues. The results showed a predisposition for change by professionals. New building projects are opportunities to question the status quo. The characterisation of the local design process and understanding the positive attitude of its architects in detail is seen here as an important, however small, step to bring about improvements in education as a whole in the conditions described.